2005
DOI: 10.1128/jvi.79.16.10126-10137.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Internal Ribosome Entry Site-Dependent Translation in Saccharomyces cerevisiae Is Independent of Polypyrimidine Tract-Binding Protein, Poly(rC)-Binding Protein 2, and La Protein

Abstract: Translation initiation of some viral and cellular mRNAs occurs by ribosome binding to an internal ribosome entry site (IRES). Internal initiation mediated by the hepatitis C virus (HCV) IRES inMost eukaryotic mRNAs are translated by a 5Ј-end-dependent mechanism, involving recruitment of the 40S ribosomal subunit by a series of interactions organized around the capbinding protein eIF4E and the 5Ј-cap structure of the mRNA. Initiation of translation of some viral and cellular mRNAs is 5Ј-end independent and occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…These results may suggest that the HCV IRES requires a certain minimal threshold of base-pairing free energy for a functional interaction and/or that three consecutive G/C bases in helix 26 are specifically required for the 18S rRNA to base pair with the HCV IRES. It may be significant that some studies have reported that the HCV IRES can function in Saccharomyces cerevisiae (32,33). The yeast 18S rRNA contains a UUU sequence in the apical loop of helix 26, which may suggest that subdomain IIId of the IRES can base pair to 18S rRNA via G−U pairing.…”
Section: Resultsmentioning
confidence: 99%
“…These results may suggest that the HCV IRES requires a certain minimal threshold of base-pairing free energy for a functional interaction and/or that three consecutive G/C bases in helix 26 are specifically required for the 18S rRNA to base pair with the HCV IRES. It may be significant that some studies have reported that the HCV IRES can function in Saccharomyces cerevisiae (32,33). The yeast 18S rRNA contains a UUU sequence in the apical loop of helix 26, which may suggest that subdomain IIId of the IRES can base pair to 18S rRNA via G−U pairing.…”
Section: Resultsmentioning
confidence: 99%
“…Rosenfeld and Racaniello (2005) claimed that cleavage of dicistronic mRNA was ruled out in their study because translation of the 3′ cistron was not reduced by mutations that inactivate the nonsense-mediated decay pathway, but that pathway is not the only source of RNases in yeast. In the case of HCV, cleavage might even occur by magnesium-catalyzed autohydrolysis (Kieft et al, 1999).…”
Section: Last Thoughtsmentioning
confidence: 97%
“…69 Plasmids. Plasmids encoding the lacZ gene of Escherichia coli (monocistronic plasmid) or the bicistronic transcript of the ADE3 gene of S. cerevisiase, the HCV IRES including sequence encoding the first 120 amino acids of the HCV polyprotein fused with the second amino acid of β-galactosidase were previously described 38 and introduced into all stains by standard cation transformation. 69 Transformation.…”
Section: Methodsmentioning
confidence: 99%
“…The requirement for two subunits of eIF3, the eIF2-GTP-Met tRNA i ternary complex, and eIF5B in HCV mediated internal initiation has been investigated using a functional assay for IRES dependent translation in S. cerevisiae. 38 Both the a and j subunits of eIF3 are needed for efficient HCV IRES dependent initiation. The absence of eIF5B abrogates internal initiation mediated by the IRES, while alteration of the eIF2-GTP-Met tRNA i ternary complex reduces translation in a concentration dependent manner.…”
Section: Introductionmentioning
confidence: 99%